Effect of the COVID-19 pandemic on the financial revenues of public hospitals with a care centre: case of the Yaoundé Central Hospital - Charles Kouanfack; Suzie Estelle Fomekong Fouakeng; Michel Foalem Nguekam; Solange Youdom Whegang; Alain Djam Chefor; Anastase Dzudie; Jérôme Ateudjieu; Eugène Sobngwi; Pierre Joseph Fouda (AOSIS, 2022)
Background: In 2020, the world was confronted with COVID-19, which caused a socio-economic panic in several sectors. The use of hospitals has been affected, with an impact on their financial performance. The objective of this study was to assess the effect of the pandemic on the financial performance of a hospital with a care center. Methodology: This was a cross-sectional study targeting the Yaoundé Central Hospital over two periods : before the pandemic (March to August 2019) and during the pandemic (March to August 2020). Based on the administrative accounts, revenues from the main sources of financial inflows were recorded and compared before and during the pandemic. Results: From March to August 2019, overall revenue was 1,131,525,099 FCFA and from March to August 2020, it was 762,770,714 FCFA, representing a drop of 32.6%. Medical imaging showed a drop of 14% corresponding to a loss of 96,500,052 FCFA. The laboratory showed a 21% decrease corresponding to a loss of 80,691,347 FCFA. Hospital admissions fell by 21%, corresponding to a loss of 62,124,675 FCFA. Consultations fell by 10%, corresponding to a loss of 49,265,835 FCFA. Conclusion: The COVID-19 pandemic had a negative effect on the financial revenues of the Yaoundé Central Hospital.